Development of wireless power transfer systems - Mohammad Nazim Atan. (2013)
Wireless Inductive Power Transfer (IPT) incorporates wireless power transfer using a set of coils to induce current from one coil to another. The contactless power delivery is achievable through the magnetic field that is created from the ever-changing current flow in the primary coil. IPT is gaining popularity in the global market, mainly due to its high efficiency of about 80%-90% and the absence of wires for hazardous or inaccessible areas.